The use of waste tyre rubber as additive for asphalt binder / Asim Hassan Ali, Nuha S.Mashaan and Mohamed Rehan Karim - Ali, Asim Hassan; S.Mashaan, Nuha; Karim, Mohamed Rehan (2012)
In recent years, polymer modified asphalt is a relatively costly material for paving roads. One way to reduce the cost of such constructions and rendering them more convenient is by using a cost-effective additive, i.e. waste rubber.Scrap tyres lead to serious disposal problems. However, the use of scrap tyres in asphalt pavements in the form of fillers/additives could improve the asphalt mixture performance properties as well as minimise environmental pollution. The main purpose of this research is to determine the effect of incorporating waste tyre rubber on the physical and mechanical properties of asphalt materials. The tests undertaken comprise the penetration test, softening point test, viscosity test and dynamic shear rheometer (DSR). The results showed that the addition of rubber has an effect on the properties of bituminous compound by increasing the viscosity, softening point, shear modulus and a decrease in penetration. Thus, the use of waste tyre rubber could improve the engineering properties of asphalt binder. Additionally, employing waste tyre rubber in sustainable technology could help to reduce some of the current pollution issue of waste tyre disposal.